Exercise Ventilatory Inefficiency Adds to Lung Function in Predicting Mortality in COPD. (3rd July 2016) - Neder, J. Alberto; Alharbi, Abdullah; Berton, Danilo C.; Alencar, Maria Clara N.; Arbex, Flavio F.; Hirai, Daniel M.; Webb, Katherine A.; O'Donnell, Denis E.
ABSTRACT: Severity of resting functional impairment only partially predicts the increased risk of death in chronic obstructive pulmonary disease (COPD). Increased ventilation during exercise is associated with markers of disease progression and poor prognosis, including emphysema extension and pulmonary vascular impairment. Whether excess exercise ventilation would add to resting lung function in predicting mortality in COPD, however, is currently unknown. After an incremental cardiopulmonary exercise test, 288 patients (forced expiratory volume in one second ranging from 18% to 148% predicted) were followed for a median (interquartile range) of 57 (47) months. Increases in the lowest (nadir) ventilation to CO2 output (VCO2 ) ratio determined excess exercise ventilation. Seventy-seven patients (26.7%) died during follow-up: 30/77 (38.9%) deaths were due to respiratory causes. Deceased patients were older, leaner, had a greater co-morbidity burden (Charlson Index) and reported more daily life dyspnea. Moreover, they had poorer lung function and exercise tolerance ( p < 0.05). A logistic regression analysis revealed that ventilation/VCO2 nadir was the only exercise variable that added to age, body mass index, Charlson Index and resting inspiratory capacity (IC)/total lung capacity (TLC) ratio to predict all-cause and respiratory mortality ( p < 0.001). Kaplan–Meier analyses showed that survival time was particularly reduced when ventilation/VCO2 nadir > 34 was associated with IC/TLC ≤ 0.34 or IC/TLC ≤ 0.31 for all-cause and respiratory mortality, respectively ( p < 0.001). Excess exercise ventilation is an independent prognostic marker across the spectrum of COPD severity. Physiological abnormalities beyond traditional airway dysfunction and lung mechanics are relevant in determining the course of the disease.